Storm Time Global Observations of Large‐Scale TIDs From Ground‐Based and In Situ Satellite Measurements. Issue 1 (4th January 2018) - Habarulema, John Bosco; Yizengaw, Endawoke; Katamzi‐Joseph, Zama T.; Moldwin, Mark B.; Buchert, Stephan
Abstract: This paper discusses the ionosphere's response to the largest storm of solar cycle 24 during 16–18 March 2015. We have used the Global Navigation Satellite Systems (GNSS) total electron content data to study large‐scale traveling ionospheric disturbances (TIDs) over the American, African, and Asian regions. Equatorward large‐scale TIDs propagated and crossed the equator to the other side of the hemisphere especially over the American and Asian sectors. Poleward TIDs with velocities in the range ≈400–700 m/s have been observed during local daytime over the American and African sectors with origin from around the geomagnetic equator. Our investigation over the American sector shows that poleward TIDs may have been launched by increased Lorentz coupling as a result of penetrating electric field during the southward turning of the interplanetary magnetic field, B z . We have observed increase in SWARM satellite electron density ( N e ) at the same time when equatorward large‐scale TIDs are visible over the European‐African sector. The altitude N e profiles from ionosonde observations show a possible link that storm‐induced TIDs may have influenced the plasma distribution in the topside ionosphere at SWARM satellite altitude. Key Points: Increased SWARM in situ electron density toward high latitudes in presence of equatorward large‐scale TIDs Evidence of equatorward TIDs in influencing altitudinal plasma distribution to the topside ionosphere Possibility of poleward TIDs launched from the geomagnetic equatorial region with comparable velocity values in both hemispheres